Antibacterial Efficacy and Cytotoxicity of Terminalia avicennioides Guill. and Perr. Stem Bark Extract Against Resistant Pathogens - Ngwu, Temiyefunolu A.; Olasunkanmi, Oluwaseun. O; Akpe, Victor; Cock, Ian Edwin (Pharmacognosy Communications, 2026)
Background: The global rise of antimicrobial resistance (AMR) has created an urgent need for alternative therapeutic agents, particularly from medicinal plants used in traditional medicine. Terminalia avicennioides Guill. and Perr. is widely used in West Africa for treating bacterial infections. Objectives: To evaluate the antibacterial efficacy and in vitro cytotoxicity of Terminalia avicennioides Guill. and Perr. stem bark extract. Materials and Methods: Stem bark was extracted using methanol-water (3:2, v/v; 60% methanol). Antibacterial activity was assessed using agar well diffusion assays, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) tests against selected Gram-positive and Gram-negative bacteria. Cytotoxicity was evaluated using the brine shrimp lethality assay (BSLA). Results: The extract produced zones of inhibition ranging from 16-22 mm at test concentrations of 30-35 mg/mL. MIC values were as low as 0.05 mg/mL against Chromobacterium spp. and 0.25 mg/mL against Staphylococcus aureus, with similar MBC values. An LC₅₀ of 820 μg/mL was determined for the extract. Conclusion: These findings validate the traditional use of Terminalia avicennioides Guill. and Perr. for bacterial infections and highlight its potential as a source of novel antimicrobial agents. Despite moderate in vitro toxicity, further in vivo studies and dosage standardization are recommended before therapeutic application.
Keywords: Antibacterial activity; Antimicrobial resistance; Brine shrimp lethality assay (BSLA); Cytotoxicity; Medicinal plants; Minimum inhibitory concentration (MIC); Phytochemical; constituents